FAKTOR-FAKTOR YANG MENYEBABKAN KETIDAKBERHASILAN IMPLEMENTASI PROGRAM PUSAT PEMBELAJARAN KELUARGA (PUSPAGA) DALAM MENEKAN KEKERASAN FISIK DAN NON FISIK BERBASIS GENDER DI KECAMATAN SEMARANG TIMUR - Shofi Salsabila Dwi Vanda; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Gender-based violence remains a serious social problem in Indonesia as it directly affects the quality of life of women, children, and family resilience. The government has introduced the Pusat Pembelajaran Keluarga Program (PUSPAGA) as a preventive effort through education, counseling, and family assistance services to reduce physical and non-physical gender-based violence. However, the implementation of this program in East Semarang District has not shown optimal results. This study aims to identify and analyze the factors that cause the unsuccessful implementation of the PUSPAGA program in reducing gender-based violence in East Semarang District. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. Research informants were determined using purposive, random, and snowball sampling techniques. Data analysis was conducted through data condensation, data presentation, and conclusion drawing, with validity testing using source and method triangulation. The results show that the suboptimal implementation of the program is influenced by five main dimensions: policy content, resources, actors, implementation context, and communication and coordination. The main obstacles include limited human resources, particularly psychologists and counselors, low intensity of socialization, and strong socio-cultural factors such as patriarchal views and the perception that domestic violence is a private matter. These conditions cause the program to focus more on case handling rather than preventive efforts. Therefore, strengthening community-based socialization, improving human resource capacity, and enhancing cross-sectoral coordination are necessary to increase the effectiveness of the PUSPAGA program in reducing gender-based violence.